Tertiary Lymphoid Structures: An Anti-tumor School for Adaptive Immune Cells and an Antibody Factory to Fight Cancer? - Teillaud, Jean-Luc; Dieu-Nosjean, Marie-Caroline (Frontiers in Immunology, 2017)
Tertiary Lymphoid Structures (TLS) present in human solid tumors are essential for the shaping of a favorable immune micro-environment to control tumor development in most cases. They represent a formidable school for T-cell priming, B cell activation and differentiation into plasma cells and an exquisitely located factory for antibody production. The manipulation of TLS neogenesis and maintenance represents therefore an exciting task to set up efficient anti-cancer vaccine strategies leading to long-lasting anti-tumor adaptive responses. To achieve this goal, a number of important issues are still pending. How TLS-T and -B cells and antibodies locally produced are related to the improved survival of cancer patients with high density of TLS is still unclear. In addition, the mechanisms by which tumors escape the immune surveillance exerted by TLS are still poorly understood and the role of immune suppressive cytokines, regulatory T cells, and/or antibodies in this process remains to be explored. The identification of the key parameters that distinguish TLS with anti- or possible pro-tumor activity is also essential to make the therapeutic targeting of TLS a success. Finally, how TLS-based therapeutic approaches can be associated with targeted therapies or immunointerventions such as the use of ICP blockers to improve anti-tumor responses, is an open question. We will discuss these different issues in the present review.